Trade and Efficiency Effects of Domestic Content Protection: The Australian Tobacco and Cigarette Industries - Beghin, John C.; Lovell, C. A. Knox (The Review of Economics and Statistics, 1993)
John C. Beghin, C. A. Knox Lovell, Trade and Efficiency Effects of Domestic Content Protection: The Australian Tobacco and Cigarette Industries, The Review of Economics and Statistics, Vol. 75, No. 4 (Nov., 1993), pp. 623-631